2016
DOI: 10.1007/s11046-016-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Voriconazole on Candida tropicalis Biofilms: Relation with ERG Genes Expression

Abstract: Candida tropicalis has emerged as the third most prevalent fungal pathogens and its ability to form biofilms has been considered one of the most important virulence factors, since biofilms represent high tolerance to antifungal agents. However, the mechanisms of C. tropicalis biofilm resistance to antifungals remain poorly understood. Thus, the main aim of this work was to infer about the effect of voriconazole on the formation and control of C. tropicalis biofilms and disclose its relationship with ERG genes'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The Candida biofilm resistance phenomenon was for the first time demonstrated in 1995 for C. albicans by Hawser and Douglas (1995) [ 6 ]. After that, the ability of Candida species biofilms to survive extraordinarily to high antifungal concentrations has been the subject of numerous investigations for many researchers [ 7 , 117 , 118 , 120 , 121 ]. So, in the last decade, additional investigations began to focus on the role of biofilm-specific traits.…”
Section: Candida Biofilms: a Real Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The Candida biofilm resistance phenomenon was for the first time demonstrated in 1995 for C. albicans by Hawser and Douglas (1995) [ 6 ]. After that, the ability of Candida species biofilms to survive extraordinarily to high antifungal concentrations has been the subject of numerous investigations for many researchers [ 7 , 117 , 118 , 120 , 121 ]. So, in the last decade, additional investigations began to focus on the role of biofilm-specific traits.…”
Section: Candida Biofilms: a Real Problemmentioning
confidence: 99%
“…Interestingly, it was observed that amphotericin B led to a significant increase of the biofilm production due to an augment of the total protein and carbohydrate contents of the matrix. Fernandes et al (2016) [ 121 ] revealed recently that voriconazole had no effect on pre-formed C. tropicalis biofilms. Remarkably, an increase in total biomass was observed when pre-formed biofilms were treated with this antifungal agent.…”
Section: Candida Biofilms: a Real Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al 38 revealed up-regulation of CDR1, MDR1, and ERG11 genes in fluconazole-nonsusceptible C. tropicalis isolates. Fernandes et al 39 showed that C. tropicalis resistance to voriconazole is unable to control biofilms, and the up-regulation of ERG genes is likely to be probable molecular mechanism of Candida biofilm resistance. The azole resistant isolate of C. tropicalis ERG11 was up-regulated, which found to be in agreement with the relatively larger amount of ergosterol in isolate.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, the increase of drug resistance to antifungals, such as fluconazole and amphotericin B during biofilm maturation, seems to be associated with a significant decrease in the total ergosterol content, with changes in the expression of some ERG genes involved in its biosynthesis compared to planktonic cells [ 87 ]. Mutations or overexpression in the ERG11 gene, which encodes lanosterol 14α-demethylase [ 88 , 89 ], as well as in other ERG genes such ERG1 (encodes squalene epoxidase), ERG3 (encodes D5,6-desaturase), ERG7 (encodes squalene cyclase), ERG9 (encodes squalene synthase) or ERG25 (encodes C-4 methyl sterol oxidase) play important roles in the resistance of fungi to different antifungal agents [ 72 , 90 , 91 , 92 ].…”
Section: Introductionmentioning
confidence: 99%